Bankart Repair With or Without Concomitant Remplissage Results in Similar Shoulder Motion and Postoperative Outcomes in the Treatment of Shoulder Instability - Ryan W. Paul, B.S; Manoj P. Reddy, M.D; Gabriel Onor, M.D; John Hayden Sonnier, M.S; Usman Zareef, B.A; Meghan E. Bishop, M.D; Brandon J. Erickson, M.D (Elsevier, 2023)
Purpose: To compare the results of patients who underwent Bankart repair with or without concomitant remplissage for treatment of shoulder instability. Methods: All patients who underwent shoulder stabilization for shoulder instability from 2014 to 2019 were evaluated. Patients who underwent remplissage were matched to those patients who received no remplissage based on sex, age, body mass index, and date of surgery. Glenoid bone loss and presence of an engaging Hill-Sachs lesion were quantified by 2 independent investigators. Postoperative complications, recurrent instability, revision, shoulder range of motion (ROM), return to sport (RTS), and patient-reported outcome measures (Oxford Shoulder Instability, Single Assessment Numeric Evaluation, and American Shoulder and Elbow Surgeons scores) were compared between groups. Results: Overall, 31 patients who underwent remplissage were identified and matched to 31 patients who received no remplissage at a mean follow-up of 2.8 ± 1.8 years. Glenoid bone loss was similar between groups (11% vs 11%, P = .956); however, engaging Hill-Sachs lesions were more prevalent in the patients who underwent remplissage than the patients who received no remplissage (84% vs 3%, P < .001). There were no significant differences in rates of redislocation (remplissage: 12.9% vs no remplissage: 9.7%), subjective instability (45.2% vs 25.8%), reoperation (12.9% vs 0%), or revision (12.9% vs 0%) between groups (all P > .05). Also, there were no differences in RTS rates, shoulder range of motion, or patient-reported outcome measures (all P > .05). Conclusions: If a patient is indicated for Bankart repair with concomitant remplissage, surgeons may expect shoulder motion and postoperative outcomes similar to those of patients without engaging Hill-Sachs lesions who undergo Bankart repair without concomitant remplissage. Level of Evidence: Therapeutic case series, level IV.